Optimizing geometric parameters for the rotor of a traction synchronous reluctance motor assisted by partitioned permanent magnets - Liubarskyi, Borys; Iakunin, Dmytro; Nikonov, Oleh; Liubarskyi, Dmytro; Yeritsyan, Bagish (Eastern-European Journal of Enterprise Technologies, 2022)
This paper considers partitioning parameters and the mutual arrangement of magnets in the rotor of the traction synchronous-jet engine with permanent partitioned magnets. The synthesis of geometrical parameters for the rotor of a synchronous reluctance motor with partitioned permanent magnets was proposed on the basis of solving the problem of conditional optimization. To solve the synthesis problem, a mathematical model has been built to determine the electromagnetic momentum of a synchronous reluctance motor with partitioned permanent magnets. It is based on the calculation of the electromagnetic momentum of the engine employing the results of a finite-element analysis of the magnetic field in the flat-parallel statement of the problem. The model is implemented in the finite-element analysis FEMM environment and makes it possible to determine the electromagnetic momentum of the engine with a variety of partitioning of permanent magnets. As an analysis problem, it is proposed to use a mathematical model of the magnetic field of the engine. The problem of conditional optimization of the rotor of a synchronous reluctance motor was stated according to the geometric criteria of the rotor. Restrictions are set on geometric, strength indicators, as well as on the level of electromagnetic momentum. The chosen optimization method is the Nelder-Mead method. Based on the results of solving the problem of synthesizing parameters for the partitioned rotor of the traction motor of trolleybus wheels, it was established that the volume of permanent magnets was reduced by 2.27 times compared to the base structure; their optimal geometric dimensions were determined (5 mm, 5.2 mm, and 5 mm), as well as the distance between them, 17.8 mm and 15.3 mm, and the engine load angle, which is 121.12 electrical degrees. Based on the results of solving the problem of synthesizing parameters for the partitioned rotor of a trolleybus traction synchronous reluctance motor, its optimal geometric parameters have been determined